Fish oil-in-water emulsions stabilized by soy proteins and cellulose nanocrystals - Di Giorgio, Luciana (2022)
This work aimed to develop fish O/W emulsions using soy protein isolate (SPI) and cellulose nanocrystals (CNC) either as separate stabilising agents or in combination. The fish O/W emulsions were prepared using aqueous dispersions containing SPI and/or different concentrations of CNC at neutral pH. The effects of each component and their concentration on the microstructure, droplet size, zeta potential, rheological behaviour, and stability of the resulting emulsions during its quiescent storage at room temperature were analysed. Emulsions prepared with both SPI and CNC showed droplets with larger sizes and surface charge than those stabilized only by SPI and were more stable than those stabilized by each component separately. The concentration of CNC determined the physicochemical and rheological properties of SPI + CNC emulsions, as well as the intervening destabilization mechanisms. Emulsion stabilized by SPI + 0.1% CNC that had a high degree of initial flocculation, turned out to be the most stable during 15 days of quiescent storage at room temperature.